Use of polymers in asphalt: a review (Gaceta Técnica, 2022)
Advances in asphalt technology lead to the search for alternative materials, which currently contribute to improve their properties and at the same time contribute to reducing environmental pollution. In this document of literary compilation of articles carried out between the years 2015 - 2021 in different databases, with the aim of knowing the benefits in the properties of asphalt mixtures, such as the optimal size, percentage of particles and improvements to the incorporate polymers. Fifty articles indexed in the ESBCO, Science Direct, ProQuest, Scielo, IOP Science, Scopus and WorldWideScience database were reviewed, on the use of polymers in asphalt mixtures, with the keywords polymers of rubber in asphalt, recycled rubber in asphalt mixtures, Influence of rubber size on asphalt, rubber for asphalt mix, Recycled Rubber; with which more information was obtained regarding the subject, concluding in this research that incorporating the polymer presents improvements in the mechanical properties of the asphalt, taking into account the percentage of polymer to be added
Keywords: asphalt mix; polymers; recycled rubber